Social Dimension of Teacher-Students Interaction in Teaching English: CDA Approach - Usaida, Esi Audya; Hasibuan, Ahmad Laut; Asnawi; Didik Santoso (PT Inovasi Pratama Internasional, 2026)
This research is driven by the significant shift in teacher roles from primary information providers to facilitators within student-centered learning models, which inherently alters classroom social dynamics. The study aims to identify the types of social dimensions in teacher-student interactions, analyze their realization through a Critical Discourse Analysis (CDA) lens, understand the underlying ideologies, and compare theoretical frameworks with actual classroom implementation. Using a qualitative approach with Critical Discourse Analysis (CDA) based on the theories of Teun A. van Dijk and Norman Fairclough, this study focuses on interactions in an eleventh-grade English class (Class XI Plus D) at SMA Negeri 1 Kutacane. Data were collected through observations of English teaching and learning sessions. The findings reveal four primary social dimensions: Power, Access, Dominance, and Control, which oscillate between hierarchical authority and collaborative engagement. While the teacher employs